Revision and phylogeny of the subaptera-group of Phyllodromica (Blattoptera: Blattellidae: Ectobiinae), including a parthenogenetic species and the evaluation of COI sequences for species identification (DNA barcoding) - Knebelsberger, Thomas; Miller, Michael A. (Zootaxa, 2007)
Until recently the subaptera-group of Phyllodromica contained only one species. The revision of the subaptera-group herein consists of the two newly described bisexual species, P. iberica and P. quadracantha, endemic to the Iberian Peninsula and a parthenogenetic species, P. subaptera (Rambur, 1838), which is widely distributed over most of the Mediterranean countries and islands. Within P. iberica three conspecific morphotypes are distinguished. The morphological characteristics of the subaptera-group are described. The species and their distributions are described and depicted. A key for the morphological determination of P. quadracantha and the morphotypes of P. iberica is given. DNA sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene are included in the species descriptions. The sequence data are suitable for species identification (DNA barcodes). A cladistic analysis of the morphological data and a phylogenetic analysis of the DNA sequences were performed to infer the phylogenetic relationships between the species of the subaptera-group.